Assessment of Knowledge, Attitude, and Practices among respiratory patients on inhalation therapy in a tertiary care hospital - Singh, Arpita; Verma, Ajay Kumar; Mandal, Ankita; Jain, Atul; Kant, Surya; Kumar, Hemant; Bajpai, Jyoti; Pandey, Anuj Kumar (Indian Journal of Community Health, 2024)
Background: Obstructive airway disease (OAD) causes significant morbidity and healthcare expenses. Smoking cessation, drug therapy, and pulmonary rehabilitation reduce morbidity and improve outcomes. However, each strategy requires knowledge, positivity, adherence, compliance, and technique to improve OAD clinical outcomes. Aim and objective: To assess the knowledge and attitude of OAD patients and to evaluate their medication adherence in a tertiary care hospital. Methodology: A north Indian tertiary care hospital conducted this six-month prospective, observational, questionnaire-based investigation. Subjects were asked questions on their disease knowledge, attitude, and drug adherence. Results: 152 patients were analyzed for this study. Here, 80 (51.9%) patients were male and 74(48.1%) were female. Among the subjects, 46.9% (n=72, p=0.0001) have adequate knowledge about their treatment and ailment. Out of the total patients, 71.2% (n=110, p=0.007) have an optimistic attitude towards their treatment, while 42.5% (n=65) of patients adhere to their therapy. Conclusion: OAD patients have low drug adherence. Simplified treatment regimens, self-management education, and provider abilities in patient education, communication, and adherence counseling can solve shortcomings.